Seroprevalencia de la teniasis y cisticercosis en escolares de la localidad El Peñón, estado Sucre. Venezuela - Guzmán Militza; Guilarte Del Valle; Urdaneta Haideé (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2004)
Abstract: Cysticercosis represents a problem of public health in geographic areas where insalubrity is present. With the objective of determining the prevalence of teniasis and cysticercosis in the town EL Peñón and its possible association with risk factors, 100 children of both sexes were studied, chosen at random, during the period September 2000 to September 2001. A survey was used to collect personal data and epidemiological data. To determined the presence of Taenia sp.eggs, fresh stool samples were collected, and were examined wet with saline physiologic solution at 0.85% using the Ritchie concentration method. Additionally 5 ml of blood were extracted from the vein to quantify specific antibodies of AbG anticysticerci by the ELISA technique, using antigens of T. crassiseps. They were no eggs of taenia sp. in the samples of stool, however, 3.00% presented levels of AbG anticysticerci equal to or higher than 1:512. The largest seroprevalence was in males (3.445), in the status V (7.14%), in the children that did not wash their hands before eating (5.17%), or after going to the bathroom (4.00%), or who drink non-treated water (5.66%), that sleep in crowded conditions (6.66%) and in children who live in houses where pigs are raised (7.14%). No statistically significant association was found between the risk factors and the presence of AbG anticisticerci. The results obtained suggest the need for epidemic surveillance in the infantile population of the community. Resumen: La cisticercosis representa un problema de salud pública en áreas geográficas donde la insa- lubridad esta presente. Con el objetivo de determinar la prevalencia de teniasis y cisticercosis en la localidad El Peñón y su posible asociación con los factores de riesgo, se estudiaron 100 escolares, de uno u otro sexo, escogidos al azar, durante el periodo Septiembre de 2000 a Septiembre 2001. A cada niño se le realizó una encuesta donde se recopilaron datos personales y datos epidemiológi- cos. Se recolectaron muestras seriadas de heces las ...